2004
DOI: 10.1260/0263617042879546
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic/Hydrophobic Properties of Silica Surfaces Modified with Metal Oxides and Polydimethylsiloxane

Abstract: Microcalorimetry and measurements of the contact angle of water were performed to investigate the hydrophilic/hydrophobic properties of silica surfaces modified with metal oxides and polydimethylsiloxane (PDMS) at 20-500°C. Fumed silicas whose surfaces contained grafted oxygen compounds of metals were used as adsorbents, with VOCl 3 , CrO 2 Cl 2 , TiCl 4 , SnCl 4 , AlCl 3 and Zn(acac) 2 vapours being applied as modifiers. It was found that the hydrophobic coating of silicas modified with metal oxides and PDMS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Similarly, other researchers also investigated the hydrophobic properties of PDMS with silica and PDMS with silica and metal oxides (Al 2 O 3 , Cr 2 O 3 , etc.) [58]. The addition of metal oxide was reported to impart a catalytic function to the reaction between the SiO 2 particles and polymer.…”
Section: Polysiloxane Based Viscoelastic Coatingsmentioning
confidence: 99%
“…Similarly, other researchers also investigated the hydrophobic properties of PDMS with silica and PDMS with silica and metal oxides (Al 2 O 3 , Cr 2 O 3 , etc.) [58]. The addition of metal oxide was reported to impart a catalytic function to the reaction between the SiO 2 particles and polymer.…”
Section: Polysiloxane Based Viscoelastic Coatingsmentioning
confidence: 99%
“…Extensive commercial utilization of polydimethylsiloxane (PDMS) polymer has been driving intense investigations of its composites upgraded with nanosized inorganic fillers. The introduction of small amounts of transition and/or rare‐earth metal nano‐oxides is known to induce significant improvements in the specific properties of the polymer, such as its thermal stability, conductivity, texture, hydrophobicity, interfacial behavior, and so on . PDMS/silica is an example of such a hybrid nanocomposite material that is already manufactured and applied at a multi‐tonnage scale.…”
Section: Introductionmentioning
confidence: 99%
“…Increased interest in studies on highly dispersed hydrophobic materials is observed due to their wide application for creation of self-cleaning hydrophobic coatings (Gaoa and Hea 2013), chemical separation of polar and non-polar substances, adsorption of organic contaminants, removal of oil from the water surface (Franco et al 2014) as well as their use as thickeners and fillers for non-polar media (Macia-Agullo et al 1995). Hydrophobic materials for these applications also must have high specific surface areas, controlled characteristics of surface hydrophobicity, high thickening efficiency and the ability to disperse in the liquid media.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate surface hydrophobicity, several methods are used; however, they all have their own advantages and limitations. The most common is a method of measuring the wetting contact angle with water Θ (Dyachenko et al 2004;Somasundaran 2006;Tarasevich et al 2002). Usually materials are considered hydrophobic if their Θ exceeds 90 degrees.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation